2015
DOI: 10.1007/s10488-015-0632-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Substance Abuse Service Engagement by Men and Women During Community Reentry Following Incarceration

Abstract: Individuals reentering the community following incarceration are at high risk for experiencing mental health and substance use problems. This longitudinal study explores patterns and barriers for engaging treatment services during early reentry. Seventy-five men and 62 women in jail, prison, or community based correctional facilities (CBCFs) participated in pre- and post-release interviews. Findings indicate that services were engaged at a lower-than-needed rate and barriers were greater for individuals leavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…Our finding that mental health, substance use, and pain management were major concerns for people on release from custody is consistent with other research [20,21,25,28,46]. Similarly, other studies have also identified stigma and discrimination [17,[19][20][21]26,28], competing priorities such as housing and employment [17][18][19][20][21][22][23], lacking access to health care and other services [17,21,22,25,26], and lack of continuity of care on release [17,21,22,24,25,40,47] as barriers to health on release. Several studies corroborate our findings regarding facilitators of health on release, including support from family and friends, access to social services, convenient and accessible health services including for opioid agonist treatment such as methadone, and service providers [17,19,23,26,40].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our finding that mental health, substance use, and pain management were major concerns for people on release from custody is consistent with other research [20,21,25,28,46]. Similarly, other studies have also identified stigma and discrimination [17,[19][20][21]26,28], competing priorities such as housing and employment [17][18][19][20][21][22][23], lacking access to health care and other services [17,21,22,25,26], and lack of continuity of care on release [17,21,22,24,25,40,47] as barriers to health on release. Several studies corroborate our findings regarding facilitators of health on release, including support from family and friends, access to social services, convenient and accessible health services including for opioid agonist treatment such as methadone, and service providers [17,19,23,26,40].…”
Section: Discussionsupporting
confidence: 90%
“…The period after release from custody is particularly challenging to health, as indicated by increased risks of morbidity and mortality [13][14][15][16]. People face urgent issues on release from jail and prison, including finding housing and employment, reconnecting with family, and meeting conditions of release [17][18][19][20][21][22][23], which may compete with addressing health and health care needs [24]. In the US, lack of health insurance poses a significant barrier to accessing health care after release, especially in states where Medicare and Medicaid are revoked upon arrest [18][19][20]23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This frequently includes several different components including full incarceration, drug and alcohol treatment, work release, community corrections, and/or long-term supervision (probation and parole). For women who are also managing a chronic illness, this transition means that they are moving from an incarceration environment where there is some limited access to healthcare services (albeit not ideal) and assistance with medications, to home situations that require them to take full responsibility for their care, often with considerably fewer resources (Begun, Early, & Hodge, 2015;Flores & Pellico, 2011).…”
Section: ▪ Backgroundmentioning
confidence: 99%